Potential uses of botanical extracts of Larrea and Grindelia in organic agriculture: Effects on soil properties and functional traits relative to growth - Lucía C. Marino; Marina Richeri; Dante Borzone; Luciana González Paleo (Ecología Austral)
Biostimulants—including botanical extracts—are natural preparations that have no negative effects on environmental health or populations and improve soil health and plant growth. Our objective was to evaluate the use of botanical extracts from two native species of the Patagonian Monte, an infusion of Larrea nitida (5%-L5 and 10%-L10) and a ferment of Grindelia chiloensis (5%-G5 and 10%-G10), on soil properties and the growth of a model plant (Triticum aestivum). While the 5% and 10% Grindelia ferments increased microbial respiration, soil N and C content, and biomass production, the 10% Larrea infusion inhibited microbial respiration and decreased total biomass. The Grindelia ferment has potential for use as a biostimulant in agroecological production, whereas the Larrea infusion does not show potential for such use. The inhibitory effect of phenolic compounds on microbial activity and plant growth should be addressed in future studies.